Vanilla distribution modeling for conservation and sustainable cultivation in a joint land sparing/sharing concept - Watteyn, Charlotte (2020)
Vanilla, an expensive but popular spice used in many industries, faces problems related to its supply. Some of these problems are due to the fact that vanilla cultivation is based on clonal material of a single species (Vanilla planifolia) and is dominated by just a few countries located outside the native grow- ing areas of aromatic vanilla species, which is the neotropics. Despite the economic importance of this crop, relatively little attention has been paid to its wild relatives, in particular with respect to their biology, ecol- ogy, and potential use. We hypothesized that species distribution models (SDMs) can identify suitable areas for both the conservation and cultivation of vanilla crop wild relatives (CWRs), following a joint land sparing/land sharing (SPASHA) approach, thus offering alternative sourcing areas and production meth- ods. This is the first study that explored the use of ensemble SDMs to provide applicable land use maps related to the conservation and sustainable cultivation of wild vanilla species in Costa Rica, contributing to a solution for the problems related to current vanilla production systems. We focused on four aromatic vanilla CWRs, native to Costa Rica, to make land use policy recommendations for this country, and more specifically for the biological corridor Osa and its surroundings within our study region Area de Conser- vacio n Osa (ACOSA). The resulting distribution maps, with a mean AUC of 0.89, reflected their current potential distribution (ranging from unsuitable to suitable) in Costa Rica. Combining them with recent land use and conservation area maps of our study region, we defined (1) areas for vanilla conservation and (2) areas for sustainable vanilla cultivation within agroforestry systems. These land use recommendations can now be integrated within the National Bio-Corridor Program (PNCB) that aims at making biological corridors more productive by proposing alternative income generation for local communities living within these areas. Our approach can be applied to identify priority areas for implementing the SPASHA approach on other vanilla CWRs and in more regions across its native growing ranges, given the availabil- ity of land use maps and enough occurrence records to build accurate SDMs.